The Representation of Love in the Dystopian Novel 1984 - Ryan Lala Rangga Senjaya (Universitas Pendidikan Indonesia (UPI), 2018)
This study aims to investigate the representation of love in George Orwell’s 1984. The data were collected from Part Two and Part Three of the book, focusing on the main characters: Winston Smith and Julia. The present study employs Rimmon-Kenan's (1983) Narratology and Sternberg's (1986) love theory as its analytical tools. The analysis shows that love is represented as three different concepts in the story: perseverance, hope, and a way of rebelling. The analysis also reveals that love is represented as the core element which contributes to the existence of rebellion in the novel. However, because of how strong the government in a dystopian setting is, love is impossible to maintain for a long time. This appears to suggest that, in a dystopian setting, any kind of hope to win against the government seems impossible to achieve. The present study is expected to provide an alternative analysis to literary worksbelonging to dystopian genre. Keywords: representation, dystopia, love, romance, George Orwell’s 1984